2008
DOI: 10.17221/360-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of daily gains of dual-purpose bulls using a random regression model

Abstract: Daily gains of 8 243 dual-purpose bulls from 100 to 400 days of age during the years 1971 to 2007 were analyzed by random regression models. Orthogonal Legendre polynomials (LP) of degree 4 were applied to daily gains calculated at 30-day intervals over the test period. Fixed curves were estimated within the station-year-season of birth. The models also included a fixed station-year-season of weighing, animal additive genetic effects and animal permanent environmental effects. The peak daily gain was attained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…All the functions had 5 parameters. A detailed description of the methodology is in Přibyl et al (2007Přibyl et al ( , 2008 and Krejčová et al (2008).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the functions had 5 parameters. A detailed description of the methodology is in Přibyl et al (2007Přibyl et al ( , 2008 and Krejčová et al (2008).…”
Section: Methodsmentioning
confidence: 99%
“…For traits from RR analysis (G1m, G2m, G3m, W1m and W1mD) the variance components for traits were derived from the covariance matrix of random regression coefficients Krejčová et al, 2008). Estimates of genetic (G) and permanent environmental (PE) components for each day during the test period were obtained by…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors (Tong et al, 1986;de Rose et al, 1988) also estimated a mean negative environmental correlation (-0.41 to -0.09) between pre-weaning growth and growth in a station test. Using the testday model with random regression, Krejčová et al (2008) also estimated negative values of r pe in bulls from Czech Fleckvieh cattle at performance test stations and documented growth compensation in those bulls influenced by the environment. Schenkel et al (2004) reported that due to the influence of the aforementioned growth compensation, the problem of correct evaluation and subsequent selection of bulls for breeding may arise.…”
Section: Direct Permanent Environmentmentioning
confidence: 99%
“…The advantages of the SSP are more pronounced for traits with lower heritabilities (Chen et al, 2011) and can be used in multiple trait (MT) analysis for the prediction of the GEBV of several traits . An SSP approach is based on typical methods using linear mixed models in large populations at a national level (Zavadilová et al, 2005(Zavadilová et al, , 2009Krejčová et al, 2008;Vostrý et al, 2008;Komprej et al, 2009), and it immediately follows all processed and programmed national-scale procedures for the genetic evaluation of farm animals (Plemdat, 2011).…”
mentioning
confidence: 99%